Strategic development vector of the flour-milling and cereal industry of Kazakhstan - Mizanbekova, S.K.; Nurmanbekova, G.K. (BUKETOV BUSINESS REVIEW, 2019)
The features of functioning of the domestic flour-milling and cereal industry are considered, in which the development of integrating associations is observed, which are based on completed technological cycle of the production of grain processing products. The activities of such enterprises depend on the material, financial, informational providing, and a new form of management opens the possibility for realization of competitive advantages of the flour-milling and cereal industry. Its economic value is determined by the ability to meet the requirements of bakery, macaroni and confectionery, alcohol and combined feed industries. It is revealed that the provision in the processing products of cereals is one of the most important tasks of state structural policy; it gives affect in the state and target complex programs. It is determined that the solution of tasks is directed to the provision of the physical and economic accessibility of foodstaff for the general population in necessary quantity and range. The integration processes in the industry are reflected, which do not show the potential due to the functions of the mechanism, which determine the production and economic relations of enterprises, while revealing the inadequacy of state support measures for processing enterprises. There is a need for the formation of a favorable management climate for the effective use of the competitive advantages of the industry. It was noted that in the milling subcomplex the growth of production capacities was carried out mainly due to the small, modular, low-investment mills. It should be noted that in the current situation, the solution of priority tasks is reduced to the uninterrupted supply of processing industries with basic raw materials — grain crops.